This page is READ-ONLY. It is generated from the old site.
All timestamps are relative to 2013 (when this page is generated).
If you are looking for TeX support, please go to VietTUG.org

Problem #697

chỉ em cách giải !!!

Added by bum almost 3 years ago. Updated over 1 year ago.

Status: Closed Start Date: 30-05-2010
Priority: Normal Due date:
Assigned to: phuoclh % Done:

80%

Category: Số học
Target version: Hè 2010
Votes: 0/0

Description

Cho a, b, c, d là các số nguyên thỏa a Chứng minh rằng:
a) a2 + b2 + c2 + d2 là tổng của ba số chính phương.
b) bc >= ad

History

Updated by tanphu almost 3 years ago

  • Subject changed from chỉ em cách giải !!! to chỉ em cách giải !!!

a) Đặt \(2e=a+d=b+c\); \(x=e-a\); \(y=e-b\)
Ta có:
\(a=e-x\)
\(b=e-y\)
\(c=2e-b=2e-(e-y)=e+y\)
\(d=2e-a=2e-(e-x)=e+x\)

Từ đó ta có:
\(a^2+b^2+c^2+d^2\)
\(=(e-x)^2+(e-y)^2+(e+x)^2+(e+y)^2\)
\(=(2e)^2+2x^2+2y^2\)
\(=(2e)^2+(x-y)^2+(x+y)^2\)

Vì \(2e\); \(x+y=2e-a-b\); \(x-y=b-a\) là các số nguyên nên \(a^2+b^2+c^2+d^2\) là tổng của ba số chính phương.

b) Ta có \(a+d=b+c\) nên:
\((a+d)^2=(b+c)^2\)
\(\Leftrightarrow a^2+d^2+2ad=b^2+c^2+2bc\)
\(\Leftrightarrow (e-x)^2+(e+x)^2+2ad=(e-y)^2+(e+y)^2+2bc\)
\(\Leftrightarrow 2e^2+2x^2+2ad=2e^2+2y^2+2bc\)
\(\Leftrightarrow x^2-y^2=bc-ad\)
\(\Leftrightarrow (x-y)(x+y)=bc-ad\)

Ta có: \(2e=a+d=b+c\)
nên: \(x=e-a=\dfrac{a+d}{2}-a=\dfrac{d-a}{2} \ge 0\) (vì theo giả thiết \(a \le d\))
tương tự: \(y=e-b=\dfrac{b+c}{2}-b=\dfrac{c-b}{2} \ge 0\) (vì theo giả thiết \(b \le c\))

Suy ra \(x \ge 0\) và \(y \ge 0\) nên \(x+y \ge 0\).

Mặt khác \(x-y=b-a \ge 0\).

Từ đó ta có \((x-y)(x+y) \ge 0 \) do đó \(bc-ad \ge 0\).

Vậy \(bc \ge ad\).

Updated by tanphu almost 3 years ago

  • Category set to Số học
  • Priority changed from Immediate to High
  • Target version set to Hè 2010
  • % Done changed from 0 to 80

Updated by tanphu over 1 year ago

  • Priority changed from High to Normal

Updated by tanphu over 1 year ago

  • Status changed from New to Closed